Pengaruh Pendapatan Premi dan Hasil Investasi Terhadap Laba Pada Perusahaan Asuransi Jiwa Syariah - Cahyani, Alfina; Septiawati, Rohma; Puspitasari, Meliana (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2023)
This study aims to examine how much influence the independent variables, namely premium income and investment returns, have on the dependent variable, namely profits at Islamic life insurance companies in Indonesia that are registered with the Financial Services Authority (OJK) for the period 2017 – 2021. Quantitative methods are used in this study with multiple linear regression data analysis techniques and processed using SPSS version 26. This study data collection technique in this research uses purposive sampling and the secondary data used are published and audited financial reports. The samples used were 7 sharia life insurance companies for research. The results prove that premium income affects profits positively and significantly, while investment returns affect profits negatively and insignificantly. However, together premium income and investment returns affect profits significantly.